Bis-allylic Deuterated DHA Alleviates Oxidative Stress in Retinal Epithelial Cells - Mélissa Rosell; Martin Giera; Philippe Brabet; Mikhail S. Shchepinov; Michel Guichardant; Thierry Durand; Joseph Vercauteren; Jean-Marie Galano; Céline Crauste (Antioxidants, 2019)
Oxidative stress plays a crucial role in developing and accelerating retinal diseases including age-related macular degeneration (AMD). Docosahexaenoic acid (DHA, C22:6, n-3), the main lipid constituent of retinal epithelial cell membranes, is highly prone to radical and enzymatic oxidation leading to deleterious or beneficial metabolites for retinal tissue. To inhibit radical oxidation while preserving enzymatic metabolism, deuterium was incorporated at specific positions of DHA, resulting in D2-DHA when incorporated at position 6 and D4-DHA when incorporated at the 6,9 bis-allylic positions. Both derivatives were able to decrease DHAs’ toxicity and free radical processes involved in lipid peroxidation, in ARPE-19 cells (Adult Retinal Pigment Epithelial cell line), under pro-oxidant conditions. Our positive results encouraged us to prepare lipophenolic-deuterated-DHA conjugates as possible drug candidates for AMD treatment. These novel derivatives proved efficient in limiting lipid peroxidation in ARPE-19 cells. Finally, we evaluated the underlying mechanisms and the enzymatic conversion of both deuterated DHA. While radical abstraction was affected at the deuterium incorporation sites, enzymatic conversion by the lipoxygenase 15s-LOX was not impacted. Our results suggest that site-specifically deuterated DHA could be used in the development of DHA conjugates for treatment of oxidative stress driven diseases, or as biological tools to study the roles, activities and mechanisms of DHA metabolites.